Dukungan sosial teman sebaya dan problem focused coping dengan stres akademik pada mahasiswa - Baiq Safitri Lestari; Alfi Purnamasari (Universitas Ahmad Dahlan, 2022)
This study aims to examine the relationship between peer social support and problem-focused coping with academic stress on psychology students at Ahmad Dahlan University, Yogyakarta. This study uses a quantitative method with a cluster random sampling technique. Collecting data using academic stress scale, peer social support scale, and problem-focused coping scale. The number of subjects who participated in this study consists of 83 students in the seventh semester from the Faculty of Psychology, Ahmad Dahlan University, Yogyakarta. The analysis used is multiple linear regression. The results of the major hypothesis test showed that peer social support and problem-focused coping had a very significant relationship with academic stress with R=0.402 and p=0.001 (p<0.01). Peer social support and problem-focused coping provide an effective contribution of 16% to academic stress. The first minor hypothesis testing showed that peer social support had a very significant negative relationship with academic stress with a significance level of p=0.008 (p<0.01) with a partial correlation value of -0.292. Peer social support provides an effective contribution of 9.169% to academic stress. Testing the second minor hypothesis showed that problem-focused coping had a significant negative relationship with academic stress with a significance level of p=0.023 (p<0.05) with a partial correlation value of -0.251. Problem-focused coping gave an effective contribution of 6.941% to academic stress.